Analyzing Mathematical Problem-Solving Skills from the Perspective of Psychological Well-Being - Zahrah, Riza; Febriani, Winarti Dwi; Wakih, Agus Ahmad; Pratiwi, Vera Ratna (IJORER : International Journal of Recent Educational Research, 2026)
Mathematical problem-solving is a fundamental competency in mathematics education that is influenced not only by cognitive ability but also by students' affective and psychological conditions. This study aimed to analyze elementary students' mathematical problem-solving skills from the perspective of psychological well-being (PWB). A mixed-methods sequential explanatory design was employed. The quantitative phase used a pre-experimental One-Group Pretest–Posttest design in which students participated in Mathematics in Context (MiC) learning. Data were collected using a mathematical problem-solving test based on Polya’s four problem-solving stages and a psychological well-being questionnaire measuring self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, and personal growth. In the qualitative phase, classroom observations and semi-structured interviews with selected students were conducted to explain and enrich the quantitative findings regarding students’ problem-solving processes and learning experiences. The quantitative results indicated a significant improvement in students’ mathematical problem-solving performance following the intervention, particularly in understanding problems, planning solution strategies, and evaluating solutions. A moderate positive correlation was also found between psychological well-being and mathematical problem-solving skills (r = 0.470, p = 0.010), indicating that students with higher psychological well-being tended to demonstrate greater persistence, confidence, and creativity when solving mathematical problems. Qualitative findings further revealed that students with higher psychological well-being showed stronger engagement, better self-regulation, and greater confidence during contextual problem-solving activities. These findings suggest that integrating Mathematics in Context with learning environments that support students’ psychological well-being contributes to improved mathematical problem-solving performance and more meaningful learning experiences.